Use of PRP in involution of canine lumbar spine osteophytes. About a clinical case (Ozone Therapy Global Journal, 2020)
A clinical case of a seven year old male canine of french poodle breed with a history of being impacted by a vehicle 2 months prior. The dog presents paresis in the hind legs as well as spinal curvature and by means of an x-ray there is espondiloarthrosis observed which has caused a decrease of the somatic spaces in the T11-T12, T12- T13, L1-L2 and L2-L3 with the presence of osteophytes in said spaces. The procedure conducted was the application of autologous PRP in a paravertebral manner with 15 day intervals for a total of 8 applications. At the conclusion of the treatment, it was observed by means of new x-ray images that the osteophytes caused by the espondiloarthrosis were reverted, there was regeneration and a visible increase in size of the intervertebral discs. These results were also reflected in the improvement of the dog’s general movements